The impact of oral hygiene instruction on plaque control in orthodontic patients: a cross-sectional study - Penoni, Daniela Cia; Moura, Milena Ferreira; Florenzano, Liliam Gusmão da Costa; Santos, Marcela Melo dos; Carlos, Juliana Cristina (Brazilian Dental Science, 2022)
Objective: Deficient dental plaque control is common in adolescents, mainly among those wearing orthodontic apparatus. This study aimed to compare plaque control and oral hygiene habits in adolescents with and without fixed orthodontic appliances. Additionally, it was investigated whether personalized oral hygiene instruction (OHI) could be a predictor for reducing dental plaque accumulation in orthodontic patients. Material and Methods: Sixty-nine patients, aged 12 to 20 years, were evaluated in a public organization which provides dental care. A questionnaire of oral hygiene habits was applied, and the number of natural teeth and number of teeth with visible biofilm were obtained during clinical examination. A comparative analysis of sociodemographic and clinical data was performed, splitting this population into two groups: those who used fixed orthodontic appliances (n=40) and those who did not (n=29). Results: There were no differences in oral hygiene habits among groups. The Poisson regression showed that adolescents with fixed appliances were 54% more likely to have dental plaque buildup compared to those who did not. Among individuals wearing orthodontic appliance, those who had not received personalized OHI before or during orthodontic treatment were 78% more likely to have a greater number of teeth with bacterial plaque compared to instructed ones. Conclusion: Especially among the adolescents wearing fixed orthodontic appliances, those who have not received personalized OHI were almost twice as likely to have a greater number of teeth with dental biofilm accumulation. Dentists and dental hygienists play a prominent role in motivating and improving the quality of individual oral hygiene. KEYWORDS Oral hygiene; Dental plaque; Orthodontic appliances; Adolescent; Prevention and control.